Reificação da mulher a partir da ascensão ideológica conservadora: uma análise do golpe de 2016 - Ferreira, Enza Rafaela Peixoto (Universidade Federal do Tocantins, 2021)
The issues surrounding the reification of women in society run through a tangle of historical and material factors, which have determined different places for men and women in socially constructed relationships. For men, the role of universal subjects, for women and feminized segments, the place of object and patient, as if this structure were part of a natural, therefore immutable form of life. These relations start from concrete constructions, and have been supported by what we understand as a heteropatriarchal capitalist system. This system has oppressed, exploited and appropriated women for centuries, taking effect since the attempt to imprison their subjectivity, as well as the product of their bodies and their work force, sometimes devalued, when the sexual division of work, sometimes invisible in the field of reproductive work and / or care. As we understand that this set of charges imposed on women is part of a social totality, manifesting itself in all dimensions and sectors of life, we arrived at this master's research, in which we seek to bare these social relations of sex, based on the particularity of 2016 coup, which removed former president Dilma from the presidency of Brazil. For this proposal, we carried out a bibliographic and documentary research, through dialogue with the critical Marxist perspective and with Francophone materialist feminists, in addition to the work of fundamental feminists regarding the analysis of women in Brazilian society. It is worth noting that the overlap between sex-race-class social relations is part of this complex. We outlined, at first, a conjunctural analysis that involves Brazilian social formation as a dialectical bridge to the present. Then, we worked on analytical categories such as ideology, conservatism, reification and patriarchy to demonstrate that this dynamic complex is intricate and reverberates in women's reification. And, finally, in the last chapter, we developed a critical analysis of the language, through the speeches given by the parliamentarians in the deliberative session of April 17, 2016, through the document of the shorthand department of the Chamber of Deputies, this one contains the entire transcript of that session. We work with the selection of excerpts of speeches that configure the existence of a misogynistic and sexist face of the coup, as when in the name of God and the traditional monogamous family, parliamentarians reiterated the need and justification for the impeachment of the stereotyped and discriminated woman president. gender, and more, for not fulfilling the “gender role” that a macho society expects of a woman. With this, we defend that language as an analytical category is constituted as one of the ideological mechanisms for the representation of concrete relations of domination and class struggle.